Ultrasonic-Microwave and Infrared Assisted Convective Drying of Carrot: Drying Kinetic, Quality and Energy Consumption - Yousef Abbaspour-Gilandeh (Applied Sciences, 2020)
In this study, the drying time, effective moisture diffusivity (Deff), specific energy consumption (SEC), and quality (color, shrinkage, and rehydration) of the ultrasound-pretreated (US) carrot slices were compared when dried by hot air drying (HD), microwave drying (MWD), infrared drying (INFD), and hybrid methods of MW–HD and INF–HD. Five mathematical models were considered to describe the drying kinetics in the carrots. The results show that US+MW–HD and INFD were the fastest and the slowest drying techniques compared to the HD technique with a 73% and 23% drying time reduction, respectively. The Deff ranged from 7.12 × 10−9 to 2.78 × 10−8 m2/s. The highest and lowest SECs were 297.29 ± 11.21 and 23.75 ± 2.22 MJ/kg which were observed in the HD and US+MWD, respectively. The color variation indices indicated that the best sample in terms of color stability was the one dried by US+MW–HD with the color variation of 11.02 ± 0.27. The lowest and highest shrinkage values were also observed in the samples dried by US+MWD and HD (31.8 ± 1.1% and 62.23 ± 1.77%), respectively. Samples dried by US+MWD and HD possessed the highest and lowest rehydration, respectively. Although the carrot slices dried at a higher pace by US+MW–HD (compared to US+MWD), the shrinkage and SEC of the samples dried by US+MWD were significantly lower than the US+MW–HD (p < 0.05). Therefore, it can be concluded that the application of the US+MWD method can be considered as a proper alternative for drying the carrot slices when compared to the HD, MWD, INFD, and hybrid methods.